(untitled) (Journal of the College of Basic Education, 2022)
The cinematic narration cannot rise without the presence of a narrator, who is responsible for narrating the events, whether it is Whether the narration is subjective or objective, the narrator remains the basis for revealing information and advancing the narration process. forward, and the narrator may be a camera or a storyteller, but in both cases he possesses Influencing the recipient to make him see the events from his own point of view, which may be different from his own. The objective point of view, if the narrator enjoys his privacy and his mental ability to convey information in a manner